TRANSPORT SEDIMEN YANG DISEBABKAN OLEH LONGSHORE CURRENT DI PANTAI KECAMATAN TELUK SEGARA KOTA BENGKULU - Supiyati Supiyati; Deddy Bakhtiar; Siti Fatimah (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Sediment transport caused by longshore current impact on the occurrence of rapid sedimentation of the coastal at Teluk Segara District Bengkulu City. The research aimed to determine the velocity of longshore current, wave energy and sediment transport happened of the coastal at Teluk Segara District which includes of the coastal at pasar Bengkulu, the coastal at Zakat, and the coastal at Pondok Besi. The method used in the research is a direct measurement in the field with the measured parameter is the height of a breaking wave, wave period, angle of breaking wave, and the velocity of longshore current. The results showed in the coastal at pasar Bengkulu average velocity of longshore current is 0.12 m/s, the wave energy is 390.16 N/m, and sediment transport is 110.956 m3/day. The coastal at Zakat average velocity of longshore current is 0.06 m/s, the wave energy is 289.52 N/m, and sediment transport is 51.085 m3/day. While the coastal at Pondok Besi average velocity of longshore current is 0.02 m/s, the wave energy is 200.20 N/m, and sediment transport is 16.026 m3/day. Keywords: Sedimentation, longshore current, wave energy, Teluk Segara.